MORAL MESSAGE IN ALIF AND ALYA'S ANIMATED FILM ”EPISODE 1-4” AS CHILDREN'S EDUCATION (RONALD BARTHES SEMIOTICS ANALYSIS) - Ali Iskandar Zulkarnain; Surawan Surawan; Siti Nur Wahidah (Universitas Muhammadiyah Surakarta, 2022)
Children are the younger generation as human resources to succeed in the ideals of the nation's struggle and the need for intellectual and moral intelligence in building national progress. One of the factors that shape children's morals is what children see. This study aims to describe the form of moral messages contained in the animated film Alif and Alya